Toward a Better Understanding of the Prior Restraint Doctrine: A Reply to Professor Mayton - HUNTER, Howard (Institutional Knowledge at Singapore Management University, 1982)
In his Article on first amendment process, Professor Mayton challenges a "sacred cow" of current first amendment theology and, in so doing, forces us to consider more carefully the implications of certain accepted approaches to the resolution of disputes about speech. Much of what he says about the process by which government restrains speech is true, especially that the prior restraint doctrine has often been inadequately understood and inappropriately invoked. Nevertheless, some of his premises are subject to question. Furthermore, his conclusion that a prior restraint model provides a better mechanism for the protection of speech than does a subsequent punishment modd 3-does not necessarily follow from his premises, nor does the conclusion reflect an adequate understanding of the prior restraint doctrine. What follows is an effort to highlight some of these problems, in the hope that the arguments presented will focus and perhaps add to Professor Mayton's discussion.